Thyroid storm following trauma: A rare case report (Indian Journal of Case Reports, 2020)
Thyroid storm, a complication of hyperthyroidism, can present with features such as altered sensorium, fever, and tachycardia. Similar features are common in trauma patients and may mask any underlying hyperthyroidism. A thorough history, recognition of risk factors, and early analysis of thyroid function in patients with unresolving fever, altered sensorium, and tachycardia can circumvent unnecessary investigations and the high mortality associated with the missed diagnosis of thyroid storm.